Tibial Plateau Injury: Mechanical Implantation with Plates and MIPO Approach Tertiary Level Hospital in Bangladesh - Rashid, Md Abdur; Ahmed, Sayed; Ahmed, Reza Nasim (Medicine Today, 2022)
Introduction: Proximal tibial injuries are challenging to treat because of articular surface involvement, frequent congestion, and precariat soft tissue conditions, particularly after high-energy traumas. The treatment is intended to restore the unity of the joint surfaces that supports the typically depressed tibial plateau cartilage, use a strong device to stabilize the fracture and prevent further damage, to enable early recovery. We describe our treatment approach, using closed or open decrease and internal fixation, polyaxy plates, automatic bone-gloss, or other osteoconductive material enhanced by autologous platelet gel, where required. Surgery depends on the timing of the soft tissue and is typically done directly or under the guidance of a skilled surgeon using tissue-sparing techniques as much as feasible. Materials and Methods: A prospective analysis of all (n=58) proximal tibial fractures at the Islamic Bank Medical College Hospital and multicentral tertiary level hospital, Rajshahi, Bangladesh, from January 2019 to June 2021. Patient data were collected by evaluating hospital diagrams, office records, preoperative and after operative radiograph. Fractures were classified in the classification of OTA/AO. In 78 % of the 12-month post-surgery group, the Rasmussen score's evaluation of functional outcomes found positive to outstanding results. Results: Total Number of patient n=58 tibial proximal (intra-articular) fractures have been identified. The mean age was 43 years (range 19–79) at surgery, whereas women and 39 men were 19. The most frequent injury mechanism was linked to traffic accidents (RTA), representing 75% of cases. 09 (18.4%) AO/OTA types A, 31 (53.5%) AO/OTA type B and 18, (31.1%) AO/OTA type C fractures have been identified. Most (90 %) cases (44) were treated with open reduction and internal fixation, using polyaxially anatomical angular stability locking Plates. Conclusions: Internal fixing using locking plates, following the MIPO principles (Minimally Invasive Percutaneous Osteosynthesis), offers an acceptable reduction of fractures with excellent outcomes for the medium-term clinical results. Medicine Today 2022 Vol.34(2): 93-98